2001
DOI: 10.1590/s0074-02762001000200005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical picture of cutaneous leishmaniases due to Leishmania (Leishmania) mexicana in the Yucatan peninsula, Mexico

Abstract: Localized cutaneous leishmaniasis (LCL), known as "chiclero´s ulcer" in southeast Mexico

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 16 publications
2
58
2
Order By: Relevance
“…In the present study the most common clinical sign, as reported in patients with LCL 4 , was a single, ulcerated, rounded small lesion, with elevated borders and necrotic center, observed in 7/36 (19.44%) of the P. yucatanicus experimentally infected with 1x10 6 L. (L.) mexicana promastigotes. Moreover, scars developed in P. yucatanicus gathered the criteria for healed lesions of humans with CL, i.e.…”
Section: This Is the First Study That Examines P Yucatanicus Clinicasupporting
confidence: 64%
See 1 more Smart Citation
“…In the present study the most common clinical sign, as reported in patients with LCL 4 , was a single, ulcerated, rounded small lesion, with elevated borders and necrotic center, observed in 7/36 (19.44%) of the P. yucatanicus experimentally infected with 1x10 6 L. (L.) mexicana promastigotes. Moreover, scars developed in P. yucatanicus gathered the criteria for healed lesions of humans with CL, i.e.…”
Section: This Is the First Study That Examines P Yucatanicus Clinicasupporting
confidence: 64%
“…The most frequently observed presentation is a single, ulcerated, rounded small lesion, with elevated borders and necrotic center, located on the ear, with an evolution time of less than three months, and with neither cutaneous metastases nor lymphatic nor mucosal involvement 4 . Criteria for scars resulting from healed lesions of humans with CL caused by Leishmania (Viannia) braziliensis include: no history of trauma, round or oval shape, smooth surface, depressed, and pigment change, hypopigmentation 38 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 92.3% of P. yucatanicus mice inoculated with 2.5 x 10 6 promastigotes developed clinical infections, with lesions similar to those found in human CL patients infected with the same parasite species (Andrade-Narváez et al 2001). This high disease rate was most likely due to the low temperature (22ºC).…”
Section: Discussionmentioning
confidence: 89%
“…Garham, 1962, is a seasonal wild zoonosis that is endemic in the Yucatan Peninsula, Mexico (Andrade-Narváez et al 2003). In this area, CL, known as "chiclero's ulcer", produces a single ulcer in 84.5% of patients and is commonly (39.9%) located on the ear lobe (Seidelin 1912, Canto-Lara et al 1998, Andrade-Narváez et al 2001. The annual incidence rate of symptomatic infection, i.e., CL, in the state of Campeche is 0.5%, whereas the subclinical infection prevalence rate is 19% (AndradeNarváez et al 1990, Arjona-Villicaña 2002.…”
mentioning
confidence: 99%
“…The clinical picture of LCL in the Yucatan Peninsula was characterized through a study performed between January 1990 and December 1995 [12]. A total of 683 patients with cutaneous lesions suggestive of LCL were examined.…”
Section: Clinical Picturementioning
confidence: 99%